2007
DOI: 10.1093/cvr/cvm089
|View full text |Cite
|
Sign up to set email alerts
|

Dystrophic cardiomyopathy: amplification of cellular damage by Ca2+ signalling and reactive oxygen species-generating pathways

Abstract: Overall, our findings reveal that excessive intracellular Ca(2+) signals and ROS generation link the initial sarcolemmal injury to mitochondrial dysfunctions. The latter possibly contribute to the loss of functional cardiac myocytes and heart failure in dystrophy. Understanding the sequence of events of dystrophic cell damage and the deleterious amplification systems involved, including several positive feed-back loops, may allow for a rational development of novel therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
150
2
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(162 citation statements)
references
References 35 publications
9
150
2
1
Order By: Relevance
“…Because I Ca-L initiates contraction in the beating heart, we propose that altered communication between I Ca-L and the mitochondria contributes to poor metabolic activity in the mdx contracting heart demonstrated as a decrease in fractional shortening on echocardiography (Table S5). Although cytosolic and mitochondrial calcium are increased in the mdx myocyte (12,32,33), we propose that altered regulation of VDAC by I Ca-L may contribute to the poor metabolic activity.…”
Section: Discussionmentioning
confidence: 80%
“…Because I Ca-L initiates contraction in the beating heart, we propose that altered communication between I Ca-L and the mitochondria contributes to poor metabolic activity in the mdx contracting heart demonstrated as a decrease in fractional shortening on echocardiography (Table S5). Although cytosolic and mitochondrial calcium are increased in the mdx myocyte (12,32,33), we propose that altered regulation of VDAC by I Ca-L may contribute to the poor metabolic activity.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, a stretch-induced increase in ROS production was completely abolished in the NOX2 knockout mice. The increased intracellular Ca 2+ response to mechanical challenge and hypersensitivity of EC coupling were normalized by both ROS scavengers and NOX inhibitors blockers (Jung et al 2007;Ullrich et al 2009;Prosser et al 2011). Taken together, and based on fact that ROS production occurs in the sarcolemmal and ttubule membranes in close proximity to NOX2, thus sensitising nearby RyRs in the SR, this may suggest that oxidation of RyRs is an early post-translational modification event in dystrophy.…”
Section: Contribution Of Oxidative Stress To Pathology In Muscular Dymentioning
confidence: 83%
“…The diaphragm muscle in the mdx mouse is highly susceptible to oxidative stress and shows a disease progression similar to human DMD (Disatnik et al 1998;Tkatchenko et al 2000;Hartel et al 2001). The damage observed in dystrophic cardiomyopathy is mainly caused by abnormalities of Ca 2+ signalling, particularly in the early stages of disease (Jung et al 2007;Prosser et al 2011). Antioxidant interventions with N-acetylcysteine in mdx mice consistently reduced ROS levels, normalized intracellular Ca 2+ levels, improved myofilament function and reduced cardiac inflammation and fibrosis (Williams and Allen 2007).…”
Section: Contribution Of Oxidative Stress To Pathology In Muscular Dymentioning
confidence: 97%
“…Moreover, it was recently reported that CaMKII can be activated in a Ca 2+ -independent way by reactive oxygen species (36). Interesting in this context is that Jung et al (23) provided evidence for increased levels of reactive oxygen species production in hearts of mdx mice.…”
Section: Discussionmentioning
confidence: 99%